Relevance and Reliability of Accounting Information in PT. Timah Tbk Financial Reports: Implications for Economic Decision Making - Putri Pudiyanti; Putri Dwi Rahmadani; Rizky Lilah Amalia; Saibatul Aslamiyah; Sylfiah Mau’izah (Indonesian Journal of Accounting and Financial Technology, 2025)
This study aims to examine the quality of accounting information within the framework of decision-making theory with a case study of PT Timah Tbk. Amidst increasingly complex modern business challenges, the accuracy and relevance of accounting information are crucial in supporting effective managerial decisions. This study uses qualitative methods by analyzing financial documents, reviewing relevant literature, and reviewing secondary data from trusted references. The results of the study indicate that the accounting information presented by PT Timah Tbk in the 2018–2019 period does not fully reflect the actual condition of the company. There were indications of data inconsistencies, revisions to financial reports, and allegations of manipulation, which led to misperceptions by investors and other stakeholders. This case also shows that weak external supervision and regulatory systems have exacerbated the impact, with estimated state losses reaching hundreds of trillions of rupiah. These findings indicate that in order for the decision-making process to run rationally and accountably, accounting information must be supported by good corporate governance and a trusted supervision system.